Heat flow data during METEOR cruise M142 - Michael Riedel; Gerhard Bohrmann (PANGAEA, 2020)
Data for estimating heat flow in the western Black Sea are provided, based on measurements made during Expedition M142 (R/V Meteor). Data are located in the Bulgarian and Romanian Sector of the Black Sea in water depths ranging from 420 to 1500 m. Data were always collected with the GEOMAR-owned 6 m long heat-probe tool, consisting of 22 Thermistors (at 26 cm spacing) along a sensor-string, a reference pressure gauge and calibration thermometer (T100 sensor). Raw data are required to be calibrated relative to the T100 sensor. Calibration data for both expeditions are provided in form of temperature offsets for each thermistor. Data provided include per station all original (raw) data for each deployment (temperature as function of time, pressure/Depth) for each thermistor, as well as initial results after separating each individual measurement sequence into penetration files (pen-files) where the temperature calibration has been applied. Results report an average thermal Gradient, heat-flux and thermal conductivity over the total penetraiton Depth of 6m. Detailed information (temperature and thermal conductivity as function of depth at each location) is given in graphical form as well as ascii data per individual penetration.